2009
DOI: 10.1016/j.desal.2008.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical pretreatment of seawater: fouling reduction and membrane characterization

Abstract: The pretreatment of raw seawater is necessary to minimize the organic fouling of seawater reverse osmosis (SWRO) membranes. To predict the membrane fouling of the pretreated seawater, the modified fouling index (MFI) with ultrafiltration (UF) was investigated in terms of molecular weight distribution (MWD) and membrane characterization. The study was conducted with seawater drawn from Collioure, France. The concentration of total dissolved solid was 32760 mg/L. The molecular weight (MW) of the initial seawater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 9 publications
(10 reference statements)
2
18
0
1
Order By: Relevance
“…Finally, in terms of MFI value, the best index was observed at 28 and 40 mL/min with the value of 2.3 × 10 4 s/L 2 . It can be explained by the correlation between the quality of treated water in terms of organic concentration and membrane fouling (Javeed et al, 2009;Shon et al, 2009). It is proved that at flow velocity of 28 mL/min, the system obtained the highest performance in terms of pollutant removal and reducing membrane fouling.…”
Section: Effect Of Flow Velocity On the Performance Of Sponge Tray Bimentioning
confidence: 97%
“…Finally, in terms of MFI value, the best index was observed at 28 and 40 mL/min with the value of 2.3 × 10 4 s/L 2 . It can be explained by the correlation between the quality of treated water in terms of organic concentration and membrane fouling (Javeed et al, 2009;Shon et al, 2009). It is proved that at flow velocity of 28 mL/min, the system obtained the highest performance in terms of pollutant removal and reducing membrane fouling.…”
Section: Effect Of Flow Velocity On the Performance Of Sponge Tray Bimentioning
confidence: 97%
“…12 Recently, an alternative indirect measurement technique for SZP of at surfaces was introduced, 13 and is comprising phase analysis light scattering (PALS) using mostly polymeric tracer particles through electro-osmotic ow (EOF) mapping in a simple dip cell arrangement. Several studies were reported on using EOF for SZP determination in a dip cell, [13][14][15][16][17][18][19][20][21] in a coated microchannel that measures the mobility of known ZP of tracer particles close to the surface, 22 in a quartz cell having mostly non-ionic hydroxypropyl-coated polystyrene tracer particles [23][24][25][26][27][28][29][30][31][32][33][34][35] or with microelectrophoresis instrumentation modied to accommodate quartz capillaries using sulphated polystyrene latex particles. 36 It relies on the principle that the electrophoretic mobility of tracer particles dispersed in a liquid is affected by the surface when these particles approach the solid sample.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, for a stateof-the-art SP analyser, these drawbacks have been overcome. On the other hand several authors have reported SZP results for various material types ( [13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35] ) obtained by the EOF method (in different congurations) using mostly polymeric tracer particles. The problems observed in these studies were associated with a high measurement uncertainty that consequently lowers the quality of the data 15,16,24,27,[38][39][40] especially for more complex sample surfaces (nanobers, membranes), difficulties in determining the surface IEP when oppositely charged tracer particles were exposed, 15,18,19,26,29 or the observation of polymeric tracer particles sedimentation and degradation (colour change of tracer particle dispersion), which is even more pronounced under elevated ionic strength, 15,19,24,28 that limits the applicability of the EOF method at high salinity conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was previously suggested that the combination of membrane fi ltration with an activated carbon pre-treatment could be a promising improvement of the fi ltration performance (especially concerning the removal of organic matter [6,7]) it was decided to technically explore this method as well, again without coagulation, as a comparable case for the stand-alone MF.…”
Section: Membranes In Drinking Andmentioning
confidence: 99%